Algorithm 804 subroutines for the computation of Mathieu Functions of Integer Orders. - Alhargan, Fayez A.
Computer subroutines in C++ for computing Mathieu functions of integer orders are described. The routines can handle a large range of the order n and the parameter h. Sample test results and graphs are given.
Keywords: Hill's determinant; Mathieu characteristic determinant; Mathieu characteristic numbers; Mathieu coefficients; Mathieu differential equation; Mathieu functions; Elliptic coordinates; Wave equation